2020
DOI: 10.1088/1742-6596/1598/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Microwave plasma torch for wound treatment

Abstract: Cold atmospheric pressure plasma (CAP) sources have recently been proven to be an effective therapeutic source regarding wound healing. The most preferred and used plasma devices at this moment are the well-known dielectric barrier discharges (DBD) and free jet devices. In this work, we studied a low temperature plasma torch at atmospheric pressure sustained by a travelling electromagnetic wave excited by surfatron type wave launcher coupled to solid state microwave generator. This plasma source allows variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…[18,22] Numerous studies demonstrated a promising use of CAP in oncology, [23][24][25] dermatology, [26][27][28] and wound healing. [29,30] In general, decontamination using plasma technologies is the most investigated and discussed topic. [31][32][33] Some studies have already gone beyond the in vitro experiments to be performed in vivo, and some have progressed to the phase of clinical trials in real patients.…”
Section: Pathogenicitymentioning
confidence: 99%
“…[18,22] Numerous studies demonstrated a promising use of CAP in oncology, [23][24][25] dermatology, [26][27][28] and wound healing. [29,30] In general, decontamination using plasma technologies is the most investigated and discussed topic. [31][32][33] Some studies have already gone beyond the in vitro experiments to be performed in vivo, and some have progressed to the phase of clinical trials in real patients.…”
Section: Pathogenicitymentioning
confidence: 99%
“…Another type of plasma source operating at atmospheric pressure and a microwave frequency of 2.45 GHz, the surface-wave-sustained discharge (SWD) was investigated for possible applications in biology, medicine, agriculture, and the food industry [24][25][26][27][28][29][30]. The specific way of plasma produced and sustained by an electromagnetic wave traveling along the plasma-dielectric interface (surface wave) determines the features of these discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Promising results are also obtained for the decontamination of seeds, plants, and fruits at a similarly short treatment time by a microwave plasma torch [28][29][30]. Some preliminary experiments on wound treatment on mice [27] also stimulate the investigations in these directions. The reactive oxygen and nitrogen (RONS) species important for bio-medical plasma effects are produced, even when the working gas is pure argon as a result of the interaction of the plasma torch with ambient air [25].…”
Section: Introductionmentioning
confidence: 99%